2017
DOI: 10.5137/1019-5149.jtn.18585-16.1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of alpha lipoic acid on motor function and antioxidant enzyme activity of nerve tissue after sciatic nerve crush injury in rats

Abstract: Conclusion: ALA that was given before crush type peripheral nerve injury provided to decrease damage of the nerve. Specific mechanisms of this effect must be clarified and must be shown that it is whether effective when it is given after injury or not.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…In recent years, ALA has been studied extensively as a biological antioxidant, detoxification agent, and antidiabetic medicine [ 1 , 5 ]. Moreover, ALA has been claimed to ameliorate age-associated cardiovascular, cognitive, and neuromuscular deficits; it has also been implicated as a modulator of various inflammatory signaling pathways [ 6 , 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, ALA has been studied extensively as a biological antioxidant, detoxification agent, and antidiabetic medicine [ 1 , 5 ]. Moreover, ALA has been claimed to ameliorate age-associated cardiovascular, cognitive, and neuromuscular deficits; it has also been implicated as a modulator of various inflammatory signaling pathways [ 6 , 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some in vivo and in vitro experimental trials showed that ALA administration increased the intracellular GSH level by 30-70%. 15 ALA antioxidant properties in vitro can be explained in different ways: 1. The concentration of ALA by conduction cell culture studies is often several folds higher than what has been seen in tissues or plasma after a per oral administration.…”
Section: Introductionmentioning
confidence: 99%
“…[30][31][32] ALA had a protective effect on mitochondrial damage and neurotoxicity caused by chemotherapeutic agents; has protective activity on nervous system lesions caused by chronic constriction injury of the peripheral nerve; topical administration of ALA in a transaction model of sciatic nerve provided faster healing; ALA that was administered 3d before ischemia resulted in a significant protective effect from moderate ischemia-reperfusion injury of the peripheral nerve. 15 The regulatory functions of ALA may now include altering protein S-nitrosylation and regulating the expression of some proteins affected by S-nitrosylation mechanisms. GSH levels were also analyzed and it is proposed that this new mechanism of ALA may be through the regulation of GSH, as this antioxidant protects mitochondrial complexes from NO-induced damage.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations